Pandangan Sekolah Terhadap Latihan Perguruan Dan Prestasi Guru Lepasan Maktab Perguruan Persekutuan Pulau Pinang - Tan , Poh Keun; D. Filmer Jr , Ivan; Mohammed, Asmah (Penerbit Universiti Sains Malaysia, 2000)
The Views Of Schools On The Training And Performance Of Teachers Trained In The Malayan Teachers College ''. The purpose of this study is to elicit the views of schools on the performance of college-trained teachers. The views of these teachers themselves were sought regarding the effectiveness of the college training in helping them to face challenges in carrying out their duties in schools.